'Candidatus phytoplasma palmicola’: a novel taxon associated with a lethal yellowing-type disease (LYD) of coconut ( Cocos nucifera L.) in Mozambique - Harrison, Nigel A.; Davis, Robert E.; Oropeza, Carlo; Helmick, Erik E.; Narvaez, Maria; Eden-Green, Simon; Dollet, Michel; Dickinson, Matthew; Konan Konan, Jean L. (Society for General Microbiology, 2014)
In this study, the taxonomic position and group classification of the phytoplasma associated with a lethal yellowing-type disease (LYD) of coconut (Cocos nucifera L.) in Mozambique were addressed. Pairwise sequence similarity values based on alignment of near full-length 16SrRNA genes (1530 bp) revealed that the Mozambique coconut phytoplasma (LYDM) shared 100% identity with a comparable sequence derived from a phytoplasma strain (LDN), responsible for Awka wilt disease of coconut in Nigeria, and shared 99-99.6% identity with 16S rRNA sequences from strains associated with Cape St. Paul wilt (CSPW) disease of coconut in Ghana and Côte d'Ivoire. Similarity scores further determined the 16S rRNA gene of LYDM phytoplasma to share <97.5% sequence identity with all prior descriptions of ‘Ca. Phytoplasma’ species. Presence of unique regions in the 16S rRNA distinguished LYDM phytoplasma from all currently described ‘Candidatus Phytoplasma’ species, justifying its recognition as reference strain of a novel taxon, ‘Candidatus Phytoplasma palmicola’. Restriction fragment length polymorphism (RFLP) profiles of the F2n/R2 portion (1251 bp) of the 16S rRNA gene and pattern similarity coefficient values delineated coconut LYDM phytoplasma strains from Mozambique as new members of established group 16SrXXII, subgroup A (16SrXXII-A). Similarity coefficients of 0.97 were obtained for comparisons between subgroup 16SrXXII-A strains and CSPW phytoplasmas from Ghana and Côte d'Ivoire. On this basis, CSPW phytoplasma strains were designated as members of a new subgroup, 16SrXXII-B.